Features of the Use of Microprocessors in the Systems of Ovojectors in their Adaptation to the Conditions of the Former CIS - Омаров, М. А.; Карташов, В. М.; Цехмистро, Р. И. (NURE, MC&FPGA, 2019)
This electronic document describes the use of microcontrollers in the regulations of automatic sorting of eggs with a live (dead) embryo with further automatic vaccination of live embryos. These installations are produced only in 3 countries and are called Ovojectors.
Keywords: microcontroller system; light sensor; mechanical extraction; computer control